Distribuição espacial do percevejo-marrom, Euschistus heros (Fabricius, 1798) (Heteroptera: Pentatomidae), na cultura da soja, utilizando geoestatística - Carvalho, João Henrique Silva [UNESP] (2014)
Euschistus heros (Fabricius, 1798) is one of the most important species from the pentatomid complex that attack soybean. It is the most abundant pentatomid in Brazil, and nymphs and adults feed on pods and seeds causing direct and irreversible damage to the commercial product. The present study aimed to study its spatial distribution using geostatistics. Thus, an experiment was carried out with the cultivar SYN1365RR in a 0.8-ha experimental field, located in Jaboticabal - SP, Brazil. The area was divided into 80 sampling units of 100 m² (10 x 10 m) each, where nymphs (1st to 5th instars), adults, and insects able to damage the seeds (nymphs from 3rd to 5th instars and adults) were sampled by the drop cloth method (1.0 x 0.5 m) on a weekly basis. Based on the geostatistical analysis of the count data, the spatial distribution of the pest in the field had an aggregated pattern from the beginning of pods (R3) to full maturity stages (R8). The spherical model was the mathematical model that best fitted the experimental semivariograms, and the range of spatial dependence (a) varied from 23.71 to 87.10 m. Regarding the spatial pattern of the pest, nymphs were moderately aggregated in the field whereas adults and stages capable of causing damage to the plants had aggregation patterns ranging from strong to moderate. Based on the kriging maps, it was possible to visualize the behavior of the pest, which started the colonization at sampling units closer to the border of the experimental area